Eustachian Valve Endocarditis: Echocardiographic Diagnosis in a Critical Care Patient - Mariana Alves; Rita Faria; António Messias; Carlos Meneses-Oliveira (Case Reports in Critical Care)
Eustachian valve endocarditis is rare. A literature review revealed that only 29 cases have been reported and, among them, there is only one mention of an intensive care unit (ICU) admission. We present an 82-year-old man without previous medical records who presented with septic shock with multiple organ dysfunction. The patient was admitted to the ICU and deteriorated with combined shock (septic + cardiogenic). A second ultrasound screen detected a prominent Eustachian valve with mobile multilobulated vegetation attached. Transesophageal echocardiography confirmed a 12 mm oscillating mass attached to a visible Eustachian valve.